ROLE OF POLYMORPHISMS OF TOLL-LIKE RECEPTORS SIGNALING PATHWAY GENES IN THE DEVELOPMENT OF HEMATOLOGICAL MALIGNANCIES - E. L. Nazarova; V. I. Shardakov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Most hematological malignancies are characterized with aberrant functioning of the immune system. The conducted studies indicate an important role in the development of malignant hematopoietic diseases arising from genetic factors, including the genes of intracellular signalling pathways, especially those involved in the implementation of an antitumor immune response. The review presents aggregated data on polymorphism studies of the toll-like receptors signalling pathway molecules of genes whose role in the development and course of various types of hematological malignancies is considered to be proven.